Identifying the Socio Economic Impact of Sports Tourism - Saputra, Sylvana Yaka; Pujiati, Amin; Runesi, Salmon; Louk, Michael Johannes Hadiwijaya; Utomo, Andy Widhiya Bayu; Puriana, Ramadhany Hananto (Indonesian Journal of Sport Management, 2025)
Background: Sports tourism is one of the strategic sectors that has great potential in encouraging economic growth and empowering local communities. However, the implementation of sports has not fully paid attention to the socio-economic conditions of the community Purpose: to examine research trends on the impact of sports tourism activities on the socio-economic Methods: The approach uses Bibbliometric analysis by reviewing 357 scientific articles sourced from Google Scholar, Scopus, and PubMed databases from 2015-2024. The publish or perish software is used to filter and sort articles and the VOSviewer software is used to analyze the articles. Overview of the gap in sports tourism development Results: There are 9 clusters of research trends in the field of sports tourism today based on the theme, namely, economic activity, economic impact, event management, socioeconomic impact, sport tourism destination, sport tourism industry, local community. Sports organizers, especially sports tourism, must be able to see the socio-cultural conditions of an area in tourism development, each region has social and cultural characteristics. Conclusion: Good sports tourism planning, synergy between the government and tourism organizations considering the social and cultural conditions of the community can provide economic benefits. Implications and Recommendation: The implication of this study is that stakeholders in formulating policies should provide full support and consider social, cultural, economic and environmental conditions in the development of the tourism industry. Sports tourism can provide benefits for the economic growth of local communities and create new jobs so that the government has a very important role in utilizing sports tourism for social, economic, cultural and sustainable tourism